Theoretical bases of innovative activity of a pedagogue - Liudmyla Mashkina (Pedagogical Discourse, 2014)
Peculiarities of innovative activity of a pedagogue have been revealed in the article. The main levels of readiness to the innovative activity in particular have been cleared up, in particular, searching, informational and creative. The main kids of readiness to the innovative activity have been shown: situational, creative, author’s, those which prepare pedagogue to solving different creative tasks. The main stages of innovative activity have been determined: origin of innovations, their mastering and routinization. The attention is accentuated on the scheme of solution making as for the innovations, in particular, formulation of pedagogical problem, its analysis, ways of solution, prognosticating and approbation.